A new species of the stenopodidean shrimp genus Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Ryukyu Islands, Indo-West Pacific - Saito, Tomomi; Fujita, Yoshihisa (Zootaxa, 2018)
A new species of the stenopodidean shrimp genus Odontozona Holthuis, 1946 is described and illustrated on the basis of 3 specimens recently collected from submarine caves of Okinawa-jima and Ie-jima Islands, the Ryukyu Islands, southwestern Japan, Indo-West Pacific. Odontozona okunoi sp. nov. closely resembles O. anaphorae Manning & Chace, 1990 described from Ascension Island, South Atlantic Ocean, but differs from it by a combination of morphological characters, including the large cardiac spine on the carapace, the spines on the pleural surface, the posterior tooth of the telson, the irregular row of small spines on the dorsomesial surface of the third pereopod chela, as well as the length ratio of the third pereopod chela against carpus and merus. This study increases the total number of species described in the genus Odontozona to 21, nine of which occur the Indo-West Pacific.